2009
DOI: 10.3800/pbr.4.104
|View full text |Cite
|
Sign up to set email alerts
|

Food sources of the oyster (Crassostrea gigas) and the clam (Ruditapes philippinarum) in the Akkeshi-ko estuary

Abstract: Abstract:The gut content was analyzed in order to clarify the potential food sources of the oyster (Crassostrea gigas) and the clam (Ruditapes philippinarum) in the Akkeshi-ko estuary. Benthic diatoms in the diets of oysters were most abundant and accounted for 70% in 2003 and 67% in 2004, followed by pelagic diatoms and dinoflagellates. In gut of clams, benthic diatoms represented 78% in 2003 and 87% in 2004, also followed by pelagic diatoms and dinoflagellates. There are no differences in dietary preference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
10
0
5
Order By: Relevance
“…In two studies on the gut contents of cultured oysters in Akkeshi-ko estuary, Kasim & Mukai [ 52 , 53 ] found that benthic diatoms (including those found on eelgrass blades) made up nearly 70% of oyster diets. These researchers also found that the composition of diatoms in the water column did not match the composition in gut contents, showing that oysters are capable of preferentially feeding on certain species of diatoms, even when they are relatively rare.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies on the gut contents of cultured oysters in Akkeshi-ko estuary, Kasim & Mukai [ 52 , 53 ] found that benthic diatoms (including those found on eelgrass blades) made up nearly 70% of oyster diets. These researchers also found that the composition of diatoms in the water column did not match the composition in gut contents, showing that oysters are capable of preferentially feeding on certain species of diatoms, even when they are relatively rare.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the enormous microalgae diversity (Parvin et al, 2007) and substantial reviews on bivalve feeding mechanisms (Gosling, 2003;Arapov et al, 2010), the knowledge on its feeding preference remains obscure (Kasim and Mukai, 2009). Yet, its microalgae selection as live feed in the hatchery, conventionally, is derived from the combination that is routinely used, regardless of bivalve species (Robert et al, 1994).…”
Section: Microalgae Selection In Bivalve Hatcherymentioning
confidence: 99%
“…Por otra parte, los especímenes revisados por los autores fueron extraidos en la zona rocosa de una isla, a 10 m de profundidad; por lo que la composición específica fue típica de ambientes oceánicos. Por su parte, la composición de la taxocenosis de diatomeas del contenido intestinal de M. gigas estuvo constituida por especies de Achnanthes, Cocconeis, Grammatophora, Melosira, Navicula, Nitzschia y Paralia (Kasim & Mukai, 2009); dicha composición es de formas típicamente epifitas; en particular es similar a la taxocenosis de diatomeas epifitas observadas sobre el pasto marino Zostera marina (Linnaeus, 1753) por Siqueiros-Beltrones et al (1987), Kasim & Mukai (2006) y Chung & Lee (2008.…”
Section: Del Componente Bentónico Solounclassified
“…64, 65 Las diatomeas ingeridas por C. corteziensis fueron mayormente de origen bentónico (72.6%), lo cual coincide con lo observado en otras especies de bivalvos filtradores como Chione gnidia Broderip & Somwerby, 1829, C. undatella G. B. Sowerby I, 1835, C. californiensis Broderip, 1835(García-Domínguez et al, 1994, Corbicula fluminea O.F. Müller, 1774 (Boltovskoy et al, 1995), Anadara tuberculosa Broderip, 1833(Muñetón-Gómez et al, 2010, R. philippinarum y M. gigas (Kasim & Mukai, 2009). Tabla 2.…”
Section: Tryblionella Hungarica (Grunow) Frenguelli Bentónicaunclassified
See 1 more Smart Citation